2015
DOI: 10.1634/theoncologist.2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Alone for Patients With Stage II/III Rectal Cancer Undergoing Radical Surgery

Abstract: Purpose. The purpose of this prospective pilot study was to determine the efficacy of preoperative chemotherapy with six cycles of FOLFOX 6 (without radiation therapy) followed by radical surgery followed by six additional cycles of FOLFOX 6 for patients with stage II/III rectal cancer. Patients and Methods. From January 2010 to January 2014, patients with locally advanced rectal cancer who met the eligibility criteria were enrolled in this study. Patients received FOLFOX 6 chemotherapy comprising oxaliplatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
7
0
2
Order By: Relevance
“…In this study, the response rate was 56.7% and the pCR rate was 6.7%. Previous studies on oxaliplatin-based regimens without a molecular-target drug revealed a pCR rate of 6.6%-12.2% (14,17,18,24). The pCR rate might increase with the addition of a molecular-target drug.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, the response rate was 56.7% and the pCR rate was 6.7%. Previous studies on oxaliplatin-based regimens without a molecular-target drug revealed a pCR rate of 6.6%-12.2% (14,17,18,24). The pCR rate might increase with the addition of a molecular-target drug.…”
Section: Discussionmentioning
confidence: 94%
“…R0 resection rate after NAC was 100% among patients who were judged to be capable of undergoing radical excision at baseline. Previous reports also showed the R0 resection rates of NAC for cT3-4 (except T4b) were high, ranging from 98.3% to 100% (11)(12)(13)(14). An important problem inherent in preoperative treatment is that surgical curability may be impaired by tumour growth during the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other chemotherapeutic agents such as irinotecan or monoclonal antibodies such as bevacizumab have not been shown to have this effect either (45). The side-effects of 5-FU based chemotherapy as single therapy or in combination with other therapies in the neoadjuvant setting are usually well tolerated with less than 5% having severe toxic reactions because of the short-term exposure (46). Current treatment schedules include nearly 6 weeks of neoadjuvant chemo radiation, 6-8 weeks of recovery prior to surgery, and another 4 weeks of recovery prior to consideration for adjuvant therapy.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Thus an alternative could be neoadjuvant chemotherapy alone. There is limited experience of chemotherapy as single treatment modality but initial reports are encouraging in terms of both down-staging and outcome but further research with long-term follow-up is needed and initiated (43,46,47). …”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%